P-BN41 Does performing percutaneous cholecystostomy in patients at risk of sepsis have better outcomes than patients in sepsis?. (16th December 2021) - Li, Wing Ching; Elboraey, Omar; Kilani, Mohammad Saeed; Ward, Jeremy Bruce; Rajendran, Ilayaraja
Abstract: Background: Gallstone related diseases account for almost one-third of acute surgical admissions with presentation varying from biliary colic to sepsis. There were various studies evaluating the role of 'percutaneous cholecystostomy' (PC) as part of the management in acute cholecystitis under 'radiological guidance' (RG). However, limited literature is conducted to evaluate patients' outcomes based on the indication and optimal timing of cholecystostomy. Therefore, this study was set up to assess the difference in clinical outcome between the patients undergoing cholecystectomy with overt sepsis (OS) and impending sepsis (IS). Methods: A retrospective observational study was conducted using a prospective database on patients who underwent PC under RG between 03/2014-03/2021. NICE's sepsis risk stratification tool was used to divide patients into OS and IS groups. OS group included patients with 1 or > 1 high-risk criteria. IS group included patients with 2 or > 2 moderate to high-risk criteria. The primary outcomes are 30-day mortality and the 'length of stay' (LoS) and secondary outcome include post-procedural 'bile leak' (BL).Continuous and categorical variables were analysed using Mann-Whitney U and Chi-squared tests respectively. A p-value of < 0.05 was considered to be statistically significant. Results: Some 27 patients were included. The median age was 80 (range 61-90).The majority of the patients (77.78%, n = 21) were unfit for surgery, with a Charlson Comorbidity Index ranging of 3 to 12. The median length of hospital stay of the OS and IS groups were 17 and 15 days respectively (p = 0.47).There was no significant difference in bile leak (IS-1/20 vs OS-0/7; p = 0.56) and drain accidents (IS-8/20 vs OS-1/7;p=0.35).Overall two patients in the IS group underwent an uncomplicated interval cholecystectomy. The 30-day mortality rate was significantly higher in OS (IS 0/20 vs OS-4/7; p = 0.00039). Conclusions: Percutaneous cholecystostomy is generally safe to be performed irrespective of patients' co-morbidities and has no significant long-term complications associated with mortality. Early cholecystostomy before overt sepsis results in a reduced 30-day mortality rate and better outcome. Further clinical studies may be required to determine specific patient groups who would benefit from percutaneous cholecystostomy.